Pemanfaatan AI sebagai Media Pembelajaran Digital dalam Foreign Language Development Program (FLDP) IAIN Madura - Rachmayanti, Irma; Alatas, Mochamad Arifin (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research is motivated by the growing development of AI technology. On the other hand, there is a Foreign Language Development Program (FLDP) at IAIN Madura. The purpose of this research is to describe the utilization of AI as a digital learning tool in the Foreign Language Development Program (FLDP) at IAIN Madura. This research is of a qualitative descriptive nature. Data is collected through questionnaires, observations, and documentation. The data sources in this study are students, instructors, and documents. The data analysis technique involves data collection, data reduction, data presentation, and inference. The results of this research provide a description of the utilization of AI as a digital learning tool in the Foreign Language Development Program (FLDP) at IAIN Madura, specifically (1) AI as a digital learning tool for Arabic language listening skills (istima’), (2) AI as a digital learning tool for Arabic language speaking skills (kalam), (3) AI as a digital learning tool for Arabic language reading skills (qiraah), and (4) AI as a digital learning tool for Arabic language writing skills (kitabah).